STRATEGI PARTAI BARU DALAM KOALISI PEMILIHAN GUBERNUR BALI 2018 - Kirana, Putu Adhismara; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACT This research aims to know the form of coalition that made of PSI towards Bali Governor Election in 2018.. This theory used is Coalition Theories by Arend Lijphart. This research uses qualitative methods with descriptive explanative type. This research find out that, coalition will form that are both connected that is, composed of parties that are adjacent on the policy scale and devoid of unnecessary partners. PSI formed a coalition by considering personal networks between political party elites where they helped communicate the party politics to form a coalition and carry Rai Mantra as a candidate for Bali Governor Election. Second, the harmonization of the DPP and DPW, where the coalition itself could not be possible if it did not get approval from DPP. Keywords : PSI, Coalition, Governor Election, Political Elite